285 Effects of maternal behavior of crossbred beef cows at calving on adjusted 205-day calf weaning weights. (7th December 2018) - Rutherford, W; Parish, J; Smith, T; Vann, R; Strickland, B
Abstract: This study objective was to assess the effect of maternal behavior at calving on calf growth performance. Crossbred beef cows (n = 309) were evaluated within 24 h of calving and assigned the following scores: 1) maternal aggression score (MA ) during calf processing (where 1 = cow not attentive to calf, flees and does not return to check on calf; 2 = cow unsure, exhibits slight interest in calf, may retreat but returns to check on calf; 3 = cow stays with calf, non-aggressive; 4 = cow very attentive, may snort or paw, vocalizes to calf; or 5 = cow very aggressive, vocalizes to humans, displays fight response); 2) mothering aptitude score (MOM ) immediately following calf processing (where 1 = cow flees without calf; 2 = cow retreats quickly with calf, may vocalize for calf, stops short distance away and nurtures calf; 3 = cow and calf flee quickly with dam chasing calf; 4 = cow checks on and then walks away with calf; or 5 = cow and calf stay in immediate area, cow licks or otherwise nurtures calf). Calf adjusted 205-d weaning BW (WW205 ) was analyzed using SAS PROC MIXED. Both MA ( P < 0.01) and MOM ( P = 0.01) affected WW205. Calves born to dams with a MA of 2 were 4.8 kg ( P = 0.03) and 6.7 kg ( P < 0.05) lighter than calves born to dams with a MA of 3 and 4, respectively. Calves born to dams with a MA of 5 were 8.3 and 9.4 kg, respectively, lighter ( P < 0.01) than those born to dams with a MA of 3 or 4. Calf WW205 was greatest ( P < 0.01) for calves born to dams with a MOM of 2. Maternal behavior at calving may influence calf growth performance through weaning.